Failure analysis of fibre metal laminate channel section column under axial compressive pulse loading - Zaczynska, Monika (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The study aims to analyse the dynamic buckling phenomenon and assess the role of the stress tensor components in the failure process of a short fibre metal laminate column under axial compressive dynamic loading. The investigation is focused on a channel-section profile composed of three aluminium layers and two doubled composite plies [Al/0/90/Al/90/0/Al]. The numerical analysis was performed on the finite element model, which was validated by experimental static buckling tests. Employing a progressive failure algorithm, this analysis incorporated the material property degradation method and Hashin’s criterion as the damage initiation criterion. Failure initiation in metal layers was based on the Huber-Mises-Hencky failure criterion. Based on the conducted analyses, it was concluded that the dominant forms of destruction in the FML structure are yielding in the metal layers due to excessive compressive stresses and the failure of the matrix in composite plies as a result of compressive and shear stresses. Through a thorough examination of the stress tensor components, critical stresses contributing to aluminium plastic deformation and laminate failure mechanisms were identified.